The Bioactivity and Phytochemicals of Pachyrhizus erosus (L.) Urb.: A Multifunctional Underutilized Crop Plant - Varun Jaiswal; Shweta Chauhan; Hae-Jeung Lee (MDPI AG, 2021)
Pachyrhizus erosus (L.) Urb. is an underutilized crop plant belonging to the Fabaceae family. In recent years, the plant received huge attention and was introduced in different countries owing to properties such as a high nutritional content, its nitrogen-fixing abilities, and different biological activities such as its antioxidant, immune modulation, anticancer, anti-diabetes, anti-osteoporosis, antiviral, and antiaging affects, among others. In this review, an attempt has been made to comprehensively compile the biological activities of the plant to provide a panoramic view of the current efforts and further directions, which may lead to the development of pharmacological applications. This information will be helpful in creating interest towards P. erosus and it may be useful in developing the plant for medical applications and/or as a functional food. More than 50 phytochemicals have been reported from the plant, which belong to different chemical classes such as triterpenoids, organic acid, flavonoids, and fatty acids. Numerous biological activities were reported from the plant through in vivo, in vitro, ex vivo, and human studies. However, well-defined clinical studies are still lacking for the establishment of any biological properties that could be further developed. Suggestions for the further development of P. erosus, according to current knowledge about the different biological properties, has also been provided.